2018
DOI: 10.2298/sos1803347l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eu3+ - dopant concentration on structural and luminescence properties of SrY2O4 nanocrystalline phosphor and potential application in dye-sensitized solar cells

Abstract: SrY 2 O 4 phosphors were doped with different concentrations of Eu 3+ (0.5, 1, 2, 4, 8 and 10 at %) in order to investigate the maximal doping concentration of Eu 3+ and its implementation in solar cell devices. Samples were synthesized by a combustion method using citric acid and glycine as a fuel. The X-ray diffraction (XRD) patterns confirmed pure phase of SrY 2 O 4. FE-SEM micrographs showed agglomerate phenomenon with spherical-like shape particles and diameter of about 50 nm. Upon excitation with 280 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Y 3+ ions are surrounded by six oxygen atoms at both places and the Sr 2+ ions are surrounded by eight oxygen atoms. [ 9,10 ] The dopant atom may substitute any of these two Y sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y 3+ ions are surrounded by six oxygen atoms at both places and the Sr 2+ ions are surrounded by eight oxygen atoms. [ 9,10 ] The dopant atom may substitute any of these two Y sites.…”
Section: Introductionmentioning
confidence: 99%
“…Y 3+ ions are surrounded by six oxygen atoms at both places and the Sr 2+ ions are surrounded by eight oxygen atoms. [9,10] The dopant atom may substitute any of these two Y sites. SrY 2 O 4 is an efficient host matrix for the doping of many rareearth ions due to similarity in ionic radii and valency.…”
mentioning
confidence: 99%
“…Binary rare earth oxides with general formula ARE 2 O 4 (A = Ca, Sr, Ba, RE = trivalent rare earth elements) are gathering significant importance for examining luminescent properties due to their specific optical, thermal and magnetic properties [7,8]. Particularly, for us is interesting SrGd 2 O 4 , although it has shown some very promising properties such as good charge stability, excellent thermal stability, refractive index (n≈2), high density (~7.3 g/cm 3 ) and high chemical robustness, it has not been extensively researched [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, some authors indicated that the luminescent properties of a host material can be improved by incorporating various metal ions. Wang et al investigated photoluminescence properties of SrGd 2 O 4 :Eu 3+ red phosphor synthesized by high-temperature solid-phase method [8]. The authors experimented with various doping concentrations of Eu 3+ (1-15 at%) and achieved the best red emission at 611 nm, caused by 5 D 0 → 7 F 2 transition (λ ex =267 nm) at 5at% Eu 3+ dopant concentration.…”
Section: Introductionmentioning
confidence: 99%